Modeling effectiveness and identification of multi-scale objects in farmland soils with improved Yee-FDTD methods - Li, Yuanhong; Zhao, Zuoxi; Qiu, Zhi; Luo, Yangfan; Zhu, Yuchan (International Journal of Agricultural and Biological Engineering, 2020)
Finite-Difference Time-Domain (FDTD) is the most popular time-domain approach in computational electromagnetics. Due to the Courant-Friedrich-Levy (CFL) condition and the perfect match layer (PML) boundary precision, FDTD cannot simulate soil medium whose surface is connected by multiple straight lines or curves (multi-scale) accurately and efficiently, which greatly limits the application of FDTD method to simulate buried objects in soils. Firstly, this study proposed the absorption boundary and adopted two typical perfect matching layers (UPML and CPML) to compare their absorption effects, and then using the three forms of improved Yee-FDTD algorithm, alternating-direction implicit (ADI-FDTD), unconditionally stable (US-FDTD) and hybrid implicit explicit finite time-domain (HIE-FDTD) to divide and contrast the boundary model effects. It showed that the HIE-FDTD was suitable for inversion of multi-scale structure object modeling, while ADI-FDTD and US-FDTD were ideal for single-boundary objects in both uniaxial perfectly matched layer (UMPL) and convolution perfectly matched layer (CPML) finite element space. After that, all the models were tested by computer performance for their simulated efficiency. When simulating single boundary objects, UPML-US-FDTD and ADI-FDTD could achieve the ideal results, and in the boundary inversion of multi-scale objects, HIE-FDTD modeling results and efficiency were the best. Test modeling speeds of CPML-HIE-FDTD were compared with three kinds of waveform sources, Ricker, Blackman-Harris and Gaussian. Finally, under the computer condition in which the CPU was i5-8250, the HIE-FDTD model still had better performance than the traditional Yee-FDTD forward modeling algorithm. For modeling multi-scale objects in farmland soils, the methods used CPML combined with the HIE-FDTD were the most efficient and accurate ways. This study can solve the problem that the traditional FDTD algorithm cannot construct non-mesh objects by utilizing the diversity characteristics of Yee cell elements. Keywords: Yee-FDTD, multi-scale objects, modeling effectiveness, Ground Penetrating Radar, farmland soils DOI: 10.25165/j.ijabe.20201306.5443 Citation: Li Y H, Zhao Z X, Qiu Z, Luo Y F, Zhu Y C. Modeling effectiveness and identification of multi-scale objects in farmland soils with improved Yee-FDTD methods. Int J Agric & Biol Eng, 2020; 13(6): 150–158.